Analgesic Effect of Intrathecal Melissa officinalis in the Rat Model of Hot-Water and Formalin-Induced Pain - Ahmad Rastegarian; Hassanali Abedi; Hossein K. Jahromi; Safar Zarei; Arash Nematollahi; Esrafil Mansouri; Hadi Sameni (Medical Association of Pharmacopuncture Institute, 2020)
Melissa officinalis (MO) is one of the oldest herbal medicines commonly used in traditional medicine, which some studies have investigated for its analgesic effect. This study is an attempt to investigate the effects of intrathecal administration of Melissa officinalis on the pain induced by heat and formalin.In this experimental study, 70 male Wistar rats with an average weight of 270-320 g were randomly divided into five groups: control; sham that received 25 μl of saline through the spinal catheter; and three experimental groups that received 5, 10 or 20 mg/kg M. officinalis via the spinal catheter respectively. Five days after catheterization of the spinal cord from the lumbar region under anesthesia, the effects of Intrathecal administration of M. officinalis on heat- and formalin-induced pain were evaluated. Data were analyzed by using one-way ANOVA. Intrathecal injection of M. officinalis blocked heat-induced pain compared to sham group (p = 0.001). Maximum analgesia was observed 30 min after the injection. Furthermore, intrathecal administration of MO alleviated both acute (p = 0.007) and chronic (p = 0.001) phases of formalin-induced pain. Motor block was not observed in any of the above mentioned groups. The results showed that intrathecal administration of MO could significantly improve hot-water and formalin-induced pain in male Wistar rats. Keywords: formalin-induced pain, heat-induced pain, intrathecal, melissa officinalis, rats